2021
DOI: 10.1038/s41467-021-22023-4
|View full text |Cite
|
Sign up to set email alerts
|

Diel niche variation in mammals associated with expanded trait space

Abstract: Mammalian life shows huge diversity, but most groups remain nocturnal in their activity pattern. A key unresolved question is whether mammal species that have diversified into different diel niches occupy unique regions of functional trait space. For 5,104 extant mammals we show here that daytime-active species (cathemeral or diurnal) evolved trait combinations along different gradients from those of nocturnal and crepuscular species. Hypervolumes of five major functional traits (body mass, litter size, diet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 66 publications
3
73
0
Order By: Relevance
“…We also lack a synthesis on the main factors shaping the different aspects of species trait spaces. The degree of organismal complexity, which is related to the diversity of cell types (Valentine et al, 1994), can indeed influence the complexity of species trait space following key functional innovation in multicellular clades (Cox et al, 2021; Knoll, 2011; Sosiak & Barden, 2021). The environment can also be crucial in determining the course of multicellular evolution and organismal complexity, with aggregative multicellularity evolving more frequently on land whereas clonal multicellularity is more frequent in water (Fisher et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also lack a synthesis on the main factors shaping the different aspects of species trait spaces. The degree of organismal complexity, which is related to the diversity of cell types (Valentine et al, 1994), can indeed influence the complexity of species trait space following key functional innovation in multicellular clades (Cox et al, 2021; Knoll, 2011; Sosiak & Barden, 2021). The environment can also be crucial in determining the course of multicellular evolution and organismal complexity, with aggregative multicellularity evolving more frequently on land whereas clonal multicellularity is more frequent in water (Fisher et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that, beyond the positive influence of species trait diversity on ecosystem functioning (Craven et al, 2018; Gross et al, 2017), these unique species can play key and irreplaceable functional roles (Le Bagousse‐Pinguet et al, 2021; Maire et al, 2018; O'Gorman et al, 2011; Pigot et al, 2016a). The filling of this trait space through evolutionary history, and more particularly the emergence of species with unique traits, has also motivated numerous studies investigating specialisation in clades or competition footprint across the tree of life (Cornwell et al, 2014; Cox et al, 2021; Jarzyna et al, 2020; Phillips et al, 2018; Ricklefs, 2010; Stubbs & Benton, 2016). Yet we still lack a flexible framework in which the number and composition of species clusters but also unique species are automatically detected regardless of the shape, the density in terms of species richness and the dimensionality of the trait space in which they are embedded.…”
Section: Introductionmentioning
confidence: 99%
“…Resource selection functions have been a popular and valuable tool to measure the relationship between available resources and animal populations, and have been used intensely in wildlife management and conservation (Strickland and McDonald, 2006). However, very little work has been done to quantify temporal habitat selection specifically (Cox et al, 2021; Gaston, 2019). Here, we built upon Farris et al (Farris et al, 2015) and developed an analytical approach to quantify temporal resource selection across environmental gradients.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that howler loud calls are rarely studied at night is not surprising because nighttime studies are, in general, underrepresented in ecological research [8,9]. For example, calls from birds and primates, two of the most studied animal taxa, are mostly studied during the day because it is easier to collect daytime data and because researchers often assume diurnal animals are not active at night, despite the lack of empirical support for this assumption [8][9][10][11][12][13][14]. Anthropoids, except the genus Aotus, are considered diurnal.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are reports of several anthropoids, such as mantled howler monkeys (Alouatta palliata), black-and-gold howler monkeys (Alouatta caraya), red-tailed monkeys (Cercopithecus ascanius), chimpanzees (Pan troglodytes), Ugandan red colobus monkeys (Procolobus rufomitratus Diversity 2021, 13, 566 2 of 12 tephrosceles), and Guianan red howler monkeys (Alouatta macconnelli) showing nocturnal activity [5,10,[14][15][16]. Diurnal sample bias [8,9] may preclude appreciation that species thought to be strictly diurnal are active during the full diel cycle [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%